Visual laboratories and fab lab in the university - Gorozhanina, Elena; Konyushenko, Svetlana; Kalimullin, Dilovar; Movchun, Vasily (Opción, 2019)
The aim of the article is to analyze and adapt the advanced experience of developed countries in the field of engineering training via comparative qualitative research methods. As a result, the social effect of Fab lab is the promotion of the development of innovative products, the creation of new jobs, the improvement of the skills of young people, the arming of technology for people to independently solve their social problems. In conclusion, the organization Fab Lab on the basis of the university can be a platform for communication between investors and developers